2015
DOI: 10.1007/s00330-014-3575-1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of oro-caecal transit time by magnetic resonance imaging

Abstract: OBJECTIVES To assess prospectively the agreement of orocaecal transit time (OCTT) measurements by lactulose hydrogen breath test (LHBT) and magnetic resonance imaging (MRI) in healthy subjects. METHODS Volunteers underwent abdominal 1.5-T MRI using axial and coronal single-shot fast-spin-echo T2-weighted sequences, having fasted and after lactulose ingestion (10 g/125 mL). Imaging and H2 excretion gas-chromatography were performed concurrently every 15 min up to 180 min. MR images were analyzed using semiautom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Reports that some IBS patients have different microbiota to non-sufferers 10,11 , and that the microbiota changes with diet, 12,13 20,21 . Luminal gas has been assessed in both the small bowel 22 and colon 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Reports that some IBS patients have different microbiota to non-sufferers 10,11 , and that the microbiota changes with diet, 12,13 20,21 . Luminal gas has been assessed in both the small bowel 22 and colon 23 .…”
Section: Discussionmentioning
confidence: 99%
“…One report quantified small bowel gas volumes to be of the order of median 49 ml (IQR 44-52 ml), the measurements carried out by using region-growing techniques in each slice with a semi-automatic method. 88 Others have used subtraction of T 1 weighted from T 2 weighted images to determine colonic gaseous content. 83 Histogram analysis can also be used to integrate the signal distribution of the chyme from black to a manually determined threshold based on signal from visible gas.…”
Section: The Evaluation Of Gi Water Content By Means Of Mrimentioning
confidence: 99%
“…Intestinal gas does not provide any MRI signal hence gas pockets can be very easily seen on abdominal MRIs. Small bowel gas volumes were measured following a lactulose challenge segmentation . The authors used a semi‐automated approach that requires clicking with the computer mouse on each gas pocket in each image; the software then grows ROIs based on intensity thresholds controlled by the operator.…”
Section: Gastrointestinal Volumesmentioning
confidence: 99%
“…A recent study showed that the median MRI OCTT was equal to the median OCTT measured with concomitant lactose ureide breath test methods, but with limited agreement between the two techniques . A similar principle was used to compare MRI OCTT and lactulose hydrogen breath test . In this case the agreement between the two techniques was better, but the median OCTTs were significantly different.…”
Section: Gastrointestinal Transitmentioning
confidence: 99%